Transcriptome analysis of mesenteric arterioles changes and its mechanisms in cirrhotic rats with portal hypertension - Guangbo Wu; Min Chen; Qiang Fan; Hongjie Li; Zhifeng Zhao; Chihao Zhang; Meng Luo (BMC Genomics)
Abstract Portal hypertension (PHT) is a major cause of liver cirrhosis. The formation of portosystemic collateral vessels and splanchnic vasodilation contribute to the development of hyperdynamic circulation, which in turn aggravates PHT and increases the risk of complications. To investigate the changes in mesenteric arterioles in PHT, cirrhotic rat models were established by ligating the common bile ducts. After 4 weeks, the cirrhotic rats suffered from severe PHT and splanchnic hyperdynamic circulation, characterized by increased portal pressure (PP), cardiac output (CO), cardiac index (CI), and superior mesenteric artery (SMA) flow. Mesenteric arterioles in cirrhotic rats displayed remarkable vasodilation, vascular remodeling, and hypocontractility. RNA sequencing was performed based on these findings. A total of 1,637 differentially expressed genes (DEGs) were detected, with 889 up-regulated and 748 down-regulated genes. Signaling pathways related to vascular changes were enriched, including the vascular endothelial growth factor (VEGF), phosphatidylinositol-3-kinase-AKT (PI3K-AKT), and nuclear factor kappa light chain enhancer of activated B cells (NF-κB) signaling pathway, among others. Moreover, the top ten hub genes were screened according to the degree nodes in the protein–protein interaction (PPI) network. Functional enrichment analyses indicated that the hub genes were involved in cell cycle regulation, mitosis, and cellular response to oxidative stress and nitric oxide (NO). In addition, promising candidate drugs for ameliorating PHT, such as resveratrol, were predicted based on hub genes. Taken together, our study highlighted remarkable changes in the mesenteric arterioles of cirrhotic rats with PHT. Transcriptome analyses revealed the potential molecular mechanisms of vascular changes in splanchnic hyperdynamic circulation.